Engagement of LGBT Teenagers in Sexting in Calapan City - Bernardo Magbanua; Ma. Arlyn Redublo (Philippine Association of Institutions for Research, Inc., 2019)
Mobile phones are essentially a part of people's lives, and it has changed the way people lead their lives.  The number is rising and the number and the way cellphones are designed today makes access to other people and different services very quick and easy. The study aimed to understand and determine the different factors leading to the engagement to sexting. The data gathering was conducted in Calapan City with members of the LGBT Community as respondents. A qualitative study was used in the collection and analysis of data. Snowball sampling was used for the one hundred (100) identified members of the LGBT community, sixty-four (64) of them have signified as engaging in sexting and twenty-three (23) agreed to be interviewed. The study found out that enjoyment and satisfaction is the factor that contributed a lot to engage in sexting.  The results showed that loss of reputation greatly affected them as individual beings. Further, what started out as simple messaging continued to implicit messaging, then sending and receiving of nude or semi-nude photos, next video chat, and for some eventually actual sex.  It is recommended that LGBT sexters should be knowledgeable about the consequences before engaging in sexting.